Muthola’ah Learning in Pesantren: Improving Learning Outcomes through Visual Media - Lalu Masaji; Ahmad Sirfi Fatoni; Mohamed Mohi El-Din Ahmad (Jurusan Pendidikan Bahasa Arab UIN Kiai Ageng Muhammad Besari onorogo, 2025)
This study aims to analyze the use of visual media in enhancing learning outcomes for TMMI second-grade students in the Muthola’ah subject at Al-Ikhlas Al-Islamy Pesantren, Kaliaji with the focus includes the effectiveness, advantages, and limitations of visual media. A qualitative approach is employed, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The informants include the principal, homeroom teacher, Muthola’ah teacher, and several TMMI second-grade students. The findings indicate that visual media significantly enhances student engagement and facilitates comprehension of the material. The learning process through visual media encompasses three key stages: preparation (planning of media and materials), implementation (core activities utilizing visual media), and evaluation (conducting written and oral assessments, along with formative and summative evaluations). The advantages of visual media include ease of access and creation, effectiveness in conveying visual messages, and assisting teachers in mastering the content. However, limitations exist, such as restricted space for media utilization and a visual appeal that is inferior to audiovisual media. This study recommends the development of more creative and contextually relevant visual-based learning media, as well as the integration of participatory strategies to enhance interactivity in the learning process. Additionally, further research is suggested to compare the effectiveness of visual media with digital media in the context of language learning within Pesantrens.